Recombinant Clotting Factors in the Treatment of Hemophilia - Lee, Christine (Thrombosis and Haemostasis, 1999)
The field of hemophilia has always been one of rapid change with improvements in clinical practice rapidly following the advances in basic science and clinical research. The major achievements of the last decade have reflected the application of molecular biology, and this has been particularly true for the development of recombinant clotting factors. The interest in developing recombinant factors VIII and IX was driven by the desire for a “safe” clotting factor following the terrible epidemics of transfusion-transmitted disease in the 1970s and 1980s.Although the goals for treatment for hemophilia, as stated by the World Federation of Hemophilia, are “to minimize disability and prolong life, to facilitate general social and physical wellbeing, and to help each patient achieve full potential, while causing no harm,”1 the cost of recombinant clotting factors are comparatively high. As a result, in many instances, the provision has been rationed, even though such therapy is considered state-of-the-art treatment for all patients requiring replacement therapy.